THE MODEL OF SMALL MOUNTAIN RESERVOIR - I. A-G. Suleymanov; A. S. Ragimova (Вестник Дагестанского государственного технического университета: Технические науки, 2016)
In the article of «The model of small mountain reservoir» with help of work out method of account of water volume of topographic explored reservoir. On the base of the studies of small mountain reservoir, profiles and form lead out dimensionless «relative complexity factor of width reservoir».